Prevalence of Aspergillus spp. and occurrence of aflatoxins in peanut sauce processing by peanut sauce manufacturers - Abdul Halim, Farawahida; Selamat, Jinap; Mahmud @ Ab Rashid, Nor Khaizura; Samsudin, Nik Iskandar Putra; Chin, Cheow Keat; Mahror, Norlia (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2020)
The aims of the present work were to determine the prevalence of Aspergillus spp. and occurrence of aflatoxins (AFs) along the peanut sauce processing line from different peanut sauce companies in Malaysia, and to determine to which extent peanut sauce processing steps employed by the peanut sauce industries could efficiently reduce AFs in peanut sauce. Peanut and chili samples were collected at each processing step along the peanut sauce production from three peanut sauce companies which were different in companies’ profile. Peanut samples from Companies B (87.5%) and C (100%) were contaminated with AFs. Of these, 12.5% (Company B) and 75% (Company C) samples exceeded the Malaysian regulatory limit. None of the samples from Company A was contaminated. The steps efficient in reducing AFs in peanut sauce identified in the present work were (i) safety monitoring of raw materials, (ii) sorting of raw materials, and (iii) heat treatment of raw materials.